Ethics, law and medical practice - Breen, Kerry J.; Plueckhahn, Vernon D.; Cordner, Stephen M. (St Leonards, NSW : Allen and Unwin, 1997)
The doctor-patient relationship. The doctor and the community. The doctor and medical practice. The doctor and the courts. Statutes impinging on medical practice.
Keywords: Australia; Law; Medical laws and legislation; Medical laws and legislation -- Australia; Medical ethics -- Australia